2018
DOI: 10.1111/and.13078
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical outcome of bilateral and unilateral varicocelectomy in infertile males with left clinical and right subclinical varicocele: A meta-analysis of randomised controlled trials

Abstract: Varicocele is the most common cause of male infertility. Varicoceles are classified into two types: clinical and subclinical varicoceles. Some researchers reported right subclinical varicoceles are often accompanied with left clinical varicoceles. However, the treatment is controversial. Our aim was to compare the clinical outcome of unilateral varicocelectomy (UV) and bilateral varicocelectomy (BV) in infertile males with left clinical and right subclinical varicocele. A total of four randomised controlled tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…Firstly, according to Trussell et al [9], up to 77.5% of infertile men with varicocele may have bilateral disease. In cases of a concurrent left clinical varicocele and right SV, bilateral varicocelectomy has been found superior to unilateral varicocelectomy for both improvement in semen parameters and increase in pregnancy rates [10]. Other anatomical aspects should also be taken into consideration, which attach extra importance to bilateral disease; Sakamoto and Ogawa [46] found that bilateral, clinical varicoceles and SVs, are much more frequently correlated with dilation of the prostatic venous plexus in comparison to unilateral SVs or no disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, according to Trussell et al [9], up to 77.5% of infertile men with varicocele may have bilateral disease. In cases of a concurrent left clinical varicocele and right SV, bilateral varicocelectomy has been found superior to unilateral varicocelectomy for both improvement in semen parameters and increase in pregnancy rates [10]. Other anatomical aspects should also be taken into consideration, which attach extra importance to bilateral disease; Sakamoto and Ogawa [46] found that bilateral, clinical varicoceles and SVs, are much more frequently correlated with dilation of the prostatic venous plexus in comparison to unilateral SVs or no disease.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a right SV is found in up to 57.8% of infertile patients with left clinical varicocele, and thus, the condition should not be disregarded [9]. Additionally, cumulative data highlight the superiority of bilateral varicocelectomy regarding higher pregnancy rates, in cases of concurrent right SV and left clinical varicocele compared to a unilateral procedure [10]. Therefore, SV may have a role in infertility.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is not clear whether bilateral surgery can bring more benefits to infertile patients with bilateral varicocele than unilateral surgery. A previously meta‐analysis (including 637 patients of left clinical with right subclinical varicocele) showed that the spontaneous pregnancy rates were higher with bilateral varicocelectomy than with unilateral varicocelectomy with an odds ratio (OR) of 1.73 (95% CI: 1.24, 2.43; Niu et al, ). And they found no significant difference involving sperm concentration (including four studies) and sperm motility (including three studies) between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, some researchers have suggested that left varicocelectomy is sufficient for patients with bilateral varicocele because the difference in the SPR between unilateral and bilateral varicocele is not significant (Zheng et al, ). A meta‐analysis conducted by Niu et al () comparing the clinical outcome of unilateral and bilateral varicocelectomy for left clinical with right subclinical varicocele showed bilateral is better than unilateral varicocelectomy. However, it only included three clinical studies and one abstract, no certain conclusion can be drawn.…”
Section: Introductionmentioning
confidence: 99%
“…The detection and management of varicocele still remains a topic of debates regarding the effects of varicocele on male fertility and, more importantly, whether repair results in an improvement of the fertility status. There are still no definite criteria enabling the selection of men who should be referred for treatment to avoid or correct defective spermatogenesis, which occurs only in a percentage of patients with varicocele (Chiba et al, ; Cho et al, ; D'Andrea et al, ; Esteves & Agarwal, ; Krause, Müller, Schäfer, & Weidner, ; Niu et al, ; Shiraishi et al, ; Sofikitis et al, ; Tavalaee, Bahreinian, Barekat, Abbasi, & Nasr‐Esfahani, ; Tisseo et al, ; Valentino et al, ; Wan, Wang, & Ji, ).…”
Section: Introductionmentioning
confidence: 99%